Productivity Analisys of Rubber Tyred Gantry Crane (TRG) and Head Truck (HT) at Makassar New Container Terminal (Terminal 1) - Zulkifli, Rifkah Fitriah; Rusnaedi Rusi; Muslihati; Andi Ningrat; Misliah; Mohammad Rizal Firmansyah (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
The increasing trend of global trade and maritime supply chain has driven container terminals to pursue operational efficiency and equipment productivity. This study aims to evaluate the productivity of Rubber Tyred Gantry Crane (RTG) and Head Truck (HT) at Makassar New Container Terminal (Terminal 1), an important logistics hub in Eastern Indonesia. Productivity was measured through direct field observation and data collection during loading and unloading operations. Five RTGs and five HTs were analyzed for a period of one hour. The level of loading and unloading productivity at Makassar New Container Terminal (Terminal 1) is categorized as good according to the Regulation of the Director General of Sea Transportation. The productivity of RTG equipment with an average unloading process of 28 container boxes/hour and a loading process of 31 container boxes/hour. Meanwhile, for HT equipment, it reaches 5 container boxes/hour for the unloading process and 7 boxes/hour for the loading process. This analysis highlights the differences in handling efficiency between equipment types, emphasizing the need for equipment optimization. These findings contribute to understanding terminal performance and support future operational improvements.